Measuring and understanding trade in service tasks - Daniel Chiquiar; Martín Tobal; Renato Yslas (Banco de México, 2016)
Improvements in Information and Communication Technologies (ICT) have had differential impacts on the costs of offshoring service tasks. As a result, services with stronger tradability characteristics are at a higher risk of being offshored. This has increased the need for coming up with proper measures of service tradability and to better understand the labor market implications of service offshoring. Indeed, recent literature suggests that both skill-intensity and tradability are key determinants of wage and employment effects. Nonetheless, the lack of widely accepted definitions of tradability, the absence of high quality data on service trade flows and the difficulty of measuring import competition at higher disaggregation levels pose difficulties to attain further empirical progress. Moreover, the theoretical literature must produce a new generation of models that could rationalize the stylized facts.
Keywords: F11; F16; 330; Service Offshoring; ICT Revolution; Trade-in-Tasks